Challenges of teaching grammar at tertiary level: learning from English lecturers' insights / Khairul Firhan Yusob - Yusob, Khairul Firhan (2018)
In the teaching of English as a second language, grammar is considered as one of the significant skills to master. However, with more attention given to other language skills, grammar is seen as the least important skill and is often taught incidentally through other skills without any proper assessment to gauge students' understanding of it. The present study highlights the challenges experienced by English lecturers in teaching grammar at undergraduate level. 15 English lecturers from a university were involved in the study as participants. They were interviewed and the data gained from the interview were transcribed and analyzed. Findings show that they faced six main challenges in teaching grammar namely lack of experience, expectations of the students, lack of facilities, negative perceptions on the teaching of grammar and preparing grammar lessons. Thus, the present study may serve as a good insight for other English lecturers as well as policy makers in overcoming the challenges.